Fatal Scopulariopsis Infection in a Lung Transplant Recipient: Lessons of Organ Procurement. Issue 12 (6th November 2014) - Shaver, C. M.; Castilho, J. L.; Cohen, D. N.; Grogan, E. L.; Miller, G. G.; Dummer, J. S.; Gray, J. N.; Lambright, E. S.; Loyd, J. E.; Robbins, I. M.
<x xml:space="preserve">Abstract</x> Seventeen days after double lung transplantation, a 56‐year‐old patient with idiopathic pulmonary fibrosis developed respiratory distress. Imaging revealed bilateral pulmonary infiltrates with pleural effusions and physical examination demonstrated sternal instability. Broad‐spectrum antibacterial and antifungal therapy was initiated and bilateral thoracotomy tubes were placed. Both right and left pleural cultures grew a mold subsequently identified as Scopulariopsis brumptii. The patient underwent pleural irrigation and sternal debridement three times but pleural and wound cultures continued to grow S. brumptii. Despite treatment with five antifungal agents, the patient succumbed to his illness 67 days after transplantation. Autopsy confirmed the presence of markedly invasive fungal disease and pleural rind formation. The patient's organ donor had received bilateral thoracostomy tubes during resuscitation in a wilderness location. There were no visible pleural abnormalities at the time of transplantation. However, the patient's clinical course and the location of the infection, in addition to the lack of similar infection in other organ recipients, strongly suggest that Scopulariopsis was introduced into the pleural space during prehospital placement of thoracostomy tubes. This case of lethal infection transmitted through transplantation highlights the unique risk of using organs from donors who are resuscitated in an outdoor location.